Grammatical errors among Hausa-speaking Arabic learners and ways to treat them - Wan Sulong, Wan Muhammad; Hassan, Abd Rauf; Ibrahim, Rabiu Abubakar (Usuli Faqih Research Centre PLT, 2024)
The aim of this study is to analyze grammatical errors among Arabic students as a second language. The objectives of the research are to identify the causes and factors that lead to its occurrence and suggest appropriate methods and strategies to overcome the problem. The research adopts a descriptive approach by using interviews. Arabic language teachers and specialists in applied linguistics are interviewed. We found the reasons why students of the Arabic language at the University of Sule Lamido, Jigawa State, make grammatical errors, They are of two types: linguistic and non-linguistic. The linguistic reasons are linguistic interference, incomplete application of the rules, false assumptions, overgeneralization, etc. As for the non-linguistic reasons, they are: students’ strategy, lack of curriculum, and failure to use appropriate modern teaching methods. After conducting the interview, appropriate methods were suggested as solutions to these problems in overcoming these errors, namely: employing and training qualified teachers, using cooperative learning and the selective method instead of the standard method, reconsidering the curriculum, and intensifying the exercises where students made mistakes.